2006
DOI: 10.1002/mrm.20930
|View full text |Cite
|
Sign up to set email alerts
|

Chromium(VI) as a novel MRI contrast agent for cerebral white matter: Preliminary results in mouse brain in vivo

Abstract: This work demonstrates that intraventricular microinjections of a low dose of potassium dichromate (0.4 L of 10 mM solution) yield a specific contrast enhancement of white matter (WM) tracts in T 1 -weighted 3D MRI of mouse brain in vivo. Pronounced and persistent signal increases (40 -100% at 24 hr after injection) were observed in the corpus callosum, anterior commissure, fornix, and stria medullaris, as well as in the mammillothalamic tract and fasciculus retroflexus. These results suggest that the extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 13 publications
2
18
2
1
Order By: Relevance
“…Distributed over the cerebrospinal and extracellular fluid of the entire central nervous system, the chelates induce a unique contrast in brain MR imaging. 19,[39][40][41][42][43] In GM, the resulting contrasts are in excellent agreement with histological stains of intracellular compounds. 19 For example, as shown in the cerebellum (Fig.…”
Section: Magnetization Transfersupporting
confidence: 63%
“…Distributed over the cerebrospinal and extracellular fluid of the entire central nervous system, the chelates induce a unique contrast in brain MR imaging. 19,[39][40][41][42][43] In GM, the resulting contrasts are in excellent agreement with histological stains of intracellular compounds. 19 For example, as shown in the cerebellum (Fig.…”
Section: Magnetization Transfersupporting
confidence: 63%
“…Cr(VI)-induced contrast leads to only a small nonspecific enhancement of gray matter structures, such as the hippocampus. Thus, this method reveals novel information that differs from that obtainable using Mn 2þ injection (73).…”
Section: Brain Agentsmentioning
confidence: 71%
“…Based on the assumption that a reduction of diamagnetic hexavalent chromium to paramagnetic Cr(III) by lipid oxidation would cause a shortening of the T 1 and T 2 of surrounding water and/or lipid protons, potassium dichromate has been studied as an MRI contrast agent (5). As reported recently, the extracellular diffusion of K 2 (Cr 2 O 7 ) after intraventricular injection leads to a mild enhancement of white matter structures (6).…”
mentioning
confidence: 69%
“…The specific oxidation of lipids exposed to aqueous solutions of potassium dichromate has been used for histologic staining of myelin (4). It has been suggested that a set of substances in the chromation, such as formaldehyde, sucrose, or hydrogen peroxide, reduces the hexavalent chromium (Cr(VI)) of the potassium dichromate to trivalent chromium (Cr(III)) (5–7). Based on the assumption that a reduction of diamagnetic hexavalent chromium to paramagnetic Cr(III) by lipid oxidation would cause a shortening of the T 1 and T 2 of surrounding water and/or lipid protons, potassium dichromate has been studied as an MRI contrast agent (5).…”
mentioning
confidence: 99%